2002
DOI: 10.1016/s0002-9440(10)64907-3
|View full text |Cite
|
Sign up to set email alerts
|

CAP37, a Novel Inflammatory Mediator

Abstract: Cationic antimicrobial protein of 37 kd (CAP37), originally isolated from human neutrophils, is an important multifunctional inflammatory mediator. Here we describe its localization within the vascular endothelium associated with atherosclerotic plaques. Evidence from in vitro immunocytochemical, Northern blot, and reverse transcriptase-polymerase chain reaction analysis indicates that CAP37 is induced in endothelial cells in response to inflammatory mediators. Endothelial-derived CAP37 shows sequence identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 29 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…MPO-generated ROS that promote endothelial cell apoptosis, tissue factor expression, low-density lipoprotein nitration, and lipid peroxidation may advance lesion development (193). Many neutrophil granule proteins, including azurocidin, LL-37, and α-defensins, are also found in human atherosclerotic lesions, suggesting that activated neutrophils may directly contribute to lesion development (194, 195). Studies in mouse models of atherosclerosis and indirect evidence in human samples suggest that many of these neutrophil-derived factors attract monocytes and influence their activation status (196).…”
Section: Neutrophils In Chronic Diseasesmentioning
confidence: 99%
“…MPO-generated ROS that promote endothelial cell apoptosis, tissue factor expression, low-density lipoprotein nitration, and lipid peroxidation may advance lesion development (193). Many neutrophil granule proteins, including azurocidin, LL-37, and α-defensins, are also found in human atherosclerotic lesions, suggesting that activated neutrophils may directly contribute to lesion development (194, 195). Studies in mouse models of atherosclerosis and indirect evidence in human samples suggest that many of these neutrophil-derived factors attract monocytes and influence their activation status (196).…”
Section: Neutrophils In Chronic Diseasesmentioning
confidence: 99%
“…We found that CAP37 was expressed in endothelial cells [71] and smooth muscle cells [63] associated with the plaque but that it was not present in normal areas of the vessel wall. Not only did these studies demonstrate the association of CAP37 an antimicrobial protein of the innate immune system with atherosclerosis but it also demonstrated the presence of an induced form of CAP37.…”
Section: Biological Significance Of Cationic Antimicrobial Peptides: mentioning
confidence: 73%
“…We investigated the biological significance of CAP37 in atherosclerosis by exploring its localization in atherosclerotic lesions [71]. We found that CAP37 was expressed in endothelial cells [71] and smooth muscle cells [63] associated with the plaque but that it was not present in normal areas of the vessel wall.…”
Section: Biological Significance Of Cationic Antimicrobial Peptides: mentioning
confidence: 99%
See 1 more Smart Citation
“…Once adhering to the vessel wall, neutrophils release soluble components such as azurocidin, which is cationic in nature and therefore favors immobilization on the endothelium, where it is presented to rolling monocytes and promotes their firm adhesion [73]. This is complemented by the capacity of azurocidin to increase expression of adhesion molecules [74,75]. Other neutrophil-borne antimicrobial peptides described to possess monocyte-attracting activity are cathepsin G [76], cathelicidins (LL37 in humans, CRAMP in mice) and defensins [77], all of which can be found in plaques [15,78].…”
Section: Neutrophils Pave the Way For Classical Monocytes In Atheroscmentioning
confidence: 99%